1999
DOI: 10.1001/archsurg.134.5.520
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Wound Healing With Topically Applied Deoxyribonucleosides

Abstract: We hypothesized that a topical mixture of purified deoxyribonucleosides would accelerate wound healing in an open wound model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…In trying to address these deficiencies, we have developed the aforementioned rabbit ear wound biofilm model, which we believe is the most accurate representation of biofilm‐infected human chronic wounds to date. Our model utilizes an adaptation of the rabbit dermal ulcer model, 21 an FDA‐recognized model of wound healing that has been utilized by our lab and others for 20 years 22–30 . In this model, full‐thickness, circular punch‐wounds are made in the ears of New Zealand White rabbits down to cartilage, affording a number of important advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In trying to address these deficiencies, we have developed the aforementioned rabbit ear wound biofilm model, which we believe is the most accurate representation of biofilm‐infected human chronic wounds to date. Our model utilizes an adaptation of the rabbit dermal ulcer model, 21 an FDA‐recognized model of wound healing that has been utilized by our lab and others for 20 years 22–30 . In this model, full‐thickness, circular punch‐wounds are made in the ears of New Zealand White rabbits down to cartilage, affording a number of important advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our knowledge of the precise cellular changes that characterize delayed healing is at present scarce, this being in part due to the lack of easily reproducible experimental models. The models described so far 30–32 do not entirely mimic the clinical problems encountered in chronic ulcers of the lower limb. Some of them involve linear incisions that obviously do not take into account wound contraction, others involve denervation, and some require the use of flaps.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo animal models have been developed to study the mechanisms of wound healing in both normal and impaired states (Rothe & Falanga, 1992). Studies have shown that topological application of cod liver oil ointment, vitamin A, deoxyribonucleosides, and some proteins can accelerate wound healing (Shah et al ., 1995; Chen et al ., 1999; Terkelsen et al ., 2000). However, up to now we know very little about the inheritance of the rate of wound healing and the mode of its inheritance.…”
Section: Introductionmentioning
confidence: 99%